1995
DOI: 10.1590/s1516-31801995000400004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of liver size by stimulation of intact rat liver with exogenous hepatotrophic factors

Abstract: In mammals, liver size is related to animal body weight at the 2.5 to 3% proportion, a ratio mediated by the afflux of hepatotrophic factors. Formulas capable of modifying this ratio have been developed in previous studies on the rat, with enhancement of liver size brought about by intraperitoneal (portal) infusion of exogenous factors such as glucose, amino acids, insulin, glucagon, vitamins, electrolytes, and triiodothyronine. However, the efficacy of these formulations was accompanied by increased animal mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
40

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(55 citation statements)
references
References 13 publications
0
15
0
40
Order By: Relevance
“…The concomitant increase in the liver weight and LC index supports this theory. In normal rats it was shown that HF promoted a 45% increase in the hepatic mass (4). The values of liver mass, volume and LC index of the control group were lower than those of the PS group (cirrhotic not treated).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…The concomitant increase in the liver weight and LC index supports this theory. In normal rats it was shown that HF promoted a 45% increase in the hepatic mass (4). The values of liver mass, volume and LC index of the control group were lower than those of the PS group (cirrhotic not treated).…”
Section: Discussionmentioning
confidence: 92%
“…The HF-treated rats showed partial restoration of the hepatic parenchyma: the lobular architecture was closer to that found in healthy animals, with an easier identification of the portal vessels and centrolobular veins. Although the effect of some components of the HF solution has been previously studied (2)(3)(4)(5), the amino acids and other nutritional components seem to act synergistically, providing the additional material and stimulus necessary to the rebuilding of the liver architecture disturbed by the cirrhotic process (6).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it has been demonstrated that the in vivo administration of NHF has a strong ability to accelerate and augment cellular proliferation as well as the growth of normal (Parra et al 1994(Parra et al , 1995, fibrotic (Cogliati et al 2010), and cirrhotic (Guerra et al 2009) liver tissues. Moreover, in fibrotic or cirrhotic livers, NHF treatment causes a reduction in the amount of tissue collagen and an improvement in the liver morphology and function (Cogliati et al 2010;Guerra et al 2009;Parra et al 1996).…”
Section: Introductionmentioning
confidence: 99%